Indoor air pollution inequalities among children and adolescents in Germany: an analysis of repeated cross-sectional data from GerES and KiGGS - Jascha Wiehn; Sarah Tietjen; Florian Beese; Wolfram Birmili; Christiane Bunge; Anja Daniels; Annika Fernandez Lahore; Domenica Hahn; Marike Kolossa-Gehring; Ronny Kuhnert; Aline Murawski; Julia Waldhauer; et al. (Scientific Reports)
Abstract Indoor air pollution may harm child health. Indoor air pollution inequalities among children and adolescents is under-researched. We analyzed associations between equivalized disposable income, socioeconomic status, and history of migration with benzene, toluene, xylene, limonene, and formaldehyde among children and adolescents in Germany. Using pooled data from the German Environmental Survey (GerES IV, GerES V) and the German Health Interview and Examination Survey for Children and Adolescents (KiGGS Baseline, KiGGS Wave 2) (N = 1117, aged 3–14 years), six out of fifteen random intercept models revealed statistically significant findings. An increase of one standard deviation in equivalized disposable income was associated with 5% lower benzene concentrations (exp(ß): 0.95, 95% confidence interval [CI] 0.91, 0.99). Higher socioeconomic status was associated with a 10% decrease in benzene (exp(ß): 0.90, 95% CI 0.87, 0.94) and a 6% decrease in toluene (exp(ß): 0.94, 95% CI 0.89, 0.99). Having a parental history of migration was associated with 24% higher concentrations of formaldehyde (exp(ß): 1.24, 95% CI 1.07, 1.43) and 102% increased limonene concentrations (exp(ß): 2.02, 95% CI 1.61, 2.55). Subgroup analysis from urban municipalities showed only slight differences. Although results varied, they highlight that indoor air pollution is unequally distributed among children and adolescents in Germany.